Detecting influencers in social media using Social Network Analysis (SNA) - Mohd Rum, Siti Nurulain; Yaakob, Razali; Affendey, Lilly Suriani (International Association of Computer Science and Information Technology, 2019)
Social media has now become a key part of life in modern society; it is a place where people share their ideas, view, emotions, and sentiments. The explosion in the popularity of social media has led to an immense increase in data over the past few years. Users engage with this platform to share their experiences, feelings, and opinions on a broad range of topics, such as politics, personalities, news, products or events. Social media has also become a phenomenal platform that provides a powerful way for businesses to enhance their prospects and reach customers. Extracting and interpreting information from user-generated content is a trending topic in the scientific community as well as in the business world, and has attracted the interest of many commercial organizations. With the wise use of social media, the marketing process for promoting products and brands can be accelerated to reach the target audience. The beauty and health industry is one of the industries that make use of this platform as their digital marketing solution to integrate communications. Recently, many leading companies and brands have used digital influencers as their strategy for marketing campaigns in management and development. Therefore, the analysis of information extracted from social media is of great importance offering valuable insights and where the importance of each actor or individual in social media can be identified. This can be achieved through the use of Social Network Analysis (SNA). This research work aims at probing the effectiveness of SNA in social media in detecting the influencers in the area of beauty and health.